SINTESIS SENYAWA ANALOG UK-3A DAN PENGARUHNYA TERHADAP BIOAKTIVITAS IN-VITRO ANTI KANKER LEUKEMIA P-388 - Husniati, -; Hanafi, Muhammad (Teknologi Indonesia, 2010)
The novel compound of analog UK-3A defi ned as 2-hydroxy-N-octylbenzamide was successfully synthesized by the amidation reaction of aromatic carboxylic acids and primary amine by adding the activator of DCC (N, N-dicyclohexylcarbodiimide), catalyst DMAP (4-dimethyl amino pyridine), and chloroform as a solvent (5 mL). The reaction held in the dean-stark device with continue stirring at 60C for 24 hours. Result shows yield as much as 93%. The structure was identifi ed using UV, FT-IR, 1H-NMR, and 13C-NMR. Bioactivity of the compound was tested in vitro against murine leukemia cancer cells P-388 by using the MTT (3 - (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide. The result of bioassay showed that this analog compound can inhibit the growth of cancer cell Murine leukemia P-388 with a higher activity than UK-3A indicated by the value of IC50 (inhibitory concentration). IC50 of analog UK-3A was found 7,5 ?g/mL whereas IC50 for UK-3A was 38 ?g/mL.